A Novel Auditory-Cognitive Training App for Delaying or Preventing the Onset of Dementia: Participatory Design With Stakeholders - Frost, Emily; Porat, Talya; Malhotra, Paresh; Picinali, Lorenzo (JMIR Human Factors, 2020)
BackgroundMultiple gaming apps exist under the dementia umbrella for skills such as navigation; however, an app to specifically investigate the role of hearing loss in the process of cognitive decline is yet to be designed. There is a demonstrable gap in the utilization of games to further the knowledge of the potential relationship between hearing loss and dementia. ObjectiveThis study aims to identify the needs, facilitators, and barriers in designing a novel auditory-cognitive training gaming app. MethodsA participatory design approach was used to engage key stakeholders across audiology and cognitive disorder specialties. Two rounds, including paired semistructured interviews and focus groups, were completed and thematically analyzed. ResultsA total of 18 stakeholders participated, and 6 themes were identified to inform the next stage of app development. These included congruence with hobbies, life getting in the way, motivational challenge, accessibility, addictive competition, and realism. ConclusionsThe findings can now be implemented in the development of the app. The app will be evaluated against outcome measures of speech listening in noise, cognitive and attentional tasks, quality of life, and usability.